2014
DOI: 10.1073/pnas.1400604111
|View full text |Cite
|
Sign up to set email alerts
|

HBx induces hypomethylation of distal intragenic CpG islands required for active expression of developmental regulators

Abstract: Epigenetic alterations caused by viral oncoproteins are strong initiation factors for cancer development, but their mechanisms are largely unknown. To identify the epigenetic effects of viral hepatitis B virus X (HBx) that lead to hepatocellular carcinoma (HCC), we profiled the DNA methylomes of normal and HBx transgenic mouse liver. Intriguingly, severe hypomethylation of intragenic CpG islands (CGIs) was observed in HBx liver before the full development of HCC. Normally, these CGIs were highly methylated (mC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 46 publications
1
57
1
1
Order By: Relevance
“…However, contrary to expectations, intragenic methylation negatively correlated with promoter methylation of the same genes, and often induced transcription [13]. Finally, intragenic CGI DNA methylation was negatively and positively related to H3K27me3 and H3K36me3 levels, respectively [14]. These results highlight the function of intragenic methylation in transcriptional activation.…”
Section: Future Science Groupcontrasting
confidence: 55%
See 1 more Smart Citation
“…However, contrary to expectations, intragenic methylation negatively correlated with promoter methylation of the same genes, and often induced transcription [13]. Finally, intragenic CGI DNA methylation was negatively and positively related to H3K27me3 and H3K36me3 levels, respectively [14]. These results highlight the function of intragenic methylation in transcriptional activation.…”
Section: Future Science Groupcontrasting
confidence: 55%
“…We observed that HBx, an oncoprotein of the hepatitis B virus, represses Dnmt3L expression, resulting in hypomethylation of intragenic CGIs [14]. The genes associated with hypomethylated intragenic CGIs in the HBx-induced liver cancer were developmental regulators related to the morphogenesis and cell adhesion, and their expression was decreased in HBx-mediated hepatocellular carcinoma.…”
Section: Intragenic Dna Methylation In Cancermentioning
confidence: 86%
“…After centrifugation, pellets were resuspended in 1ϫ TE buffer containing an EDTA-free protease inhibitor cocktail (Roche) and sonicated in a UP200S sonication device with 5 cycles at an amplitude of 50%, a 0.5-s pulse during 30 s, and 30 s on ice. Lysates were centrifuged and diluted with 2ϫ radioimmunoprecipitation assay (RIPA) buffer (10 mM Tris-Cl [pH 7.6], 1 mM EDTA [pH 8.0], 0.1% Na-deoxycholate, 1% Triton X-100, and an EDTA-free protease inhibitor cocktail [Roche]) (28). Chromatin was subjected to immunoprecipitation overnight at 4°C with 3 g of nonspecific immunoglobulins (Sigma) as a negative control, an anti-H4 antibody (Active Motif) as a positive control, or an anti-DDB1 antibody (Santa Cruz).…”
Section: Methodsmentioning
confidence: 99%
“…Genome-wide DNA methylation [49], histone methylations (H3K4Me3, H3K27Me3, and H3K36Me3), and serine 2 and 5 phosphorylation of RNA polymerase II were profiled from the livers of 3-month old wild-type and HBx transgenic (TG) mice. The gene expression data were downloaded from the Gene Expression Omnibus (GEO accession number: GSE48052 for RNA-Seq [49]).…”
Section: Methodsmentioning
confidence: 99%